C-reactive protein point-of-care testing and complementary strategies to improve antibiotic stewardship in children with acute respiratory infections in primary care - Staiano, Annamaria; Bjerrum, Lars; Llor, Carl; Melbye, Hasse; Hopstaken, Rogier; Gentile, Ivan; Plate, Andreas; van Hecke, Oliver; Verbakel, Jan Y. (Frontiers in Pediatrics, 2023)
This paper provides the perspective of an international group of experts on the role of C-reactive protein (CRP) point-of-care testing (POCT) and complementary strategies such as enhanced communication skills training and delayed prescribing to improve antibiotic stewardship in the primary care of children presenting with an acute illness episode due to an acute respiratory tract infection (ARTI).To improve antibiotics prescribing decisions, CRP POCT should be considered to complement the clinical assessment of children (6 months to 14 years) presenting with an ARTI in a primary care setting. CRP POCT can help decide whether a serious infection can be ruled out, before deciding on further treatments or management, when clinical assessment is unconclusive. Based on the evidence currently available, a CRP value can be a valuable support for clinical reasoning and facilitate communication with patients and parents, but the clinical assessment should prevail when making a therapy or referral decision. Nearly half of children tested in the primary care setting can be expected to have a CRP value below 20 mg/L, in which case it is strongly suggested to avoid prescribing antibiotics when the clinical assessment supports ruling out a severe infection. For children with CRP values greater than or equal to 20 mg/L, additional measures such as additional diagnostic tests, observation time, re-assessment by a senior decision-maker, and specialty referrals, should be considered.